Star wars. a new hope Episode IV. - Lucas, George; Kurtz, Gary.; Lucasfilm, Ltd.; Twentieth Century-Fox Film Corporation; Twentieth Century Fox Home Entertainment, Inc. (Hollywood, Calif. Lucasfilm Ltd, 2000)
Princess Leia is captured and held hostage by the evil Imperial forces in their effort to take over the galactic Empire. Luke Skywalker, Han Solo, and two robots (R2-D2 and C-3PO) work together to rescue the princess and restore justice in the Empire.
Originally released as a motion picture in 1983.
Issued in a case with star wars, episode V : the empire strikes back ; episode VI : return of the jedi.
Director of photography, Gilbert Taylor; editors, Richard Chew . . [et al.]; music, John Williams.
Harrison Ford, Carrie Fisher, Mark Hamill, James Earl Jones, Billy Dee Williams, Alec Guinness, Peter Cushing, Anthony Daniels, Kenny Baker, David Prowse.
MPAA rating: PG.
VCD
Keywords: Skywalker, Luke -- (Fictitious character) -- Drama; Organa, Leia -- (Fictitious character) -- Drama; Solo, Han -- (Fictitious character) -- Drama; Life on other planets -- Drama; Good and evil -- Drama